Food insecurity and coping strategies index among low-income households in Klang Valley, Malaysia - Ahmad Azuddin, Ainatul Husna; Ramli, Nurul Nadia; Shamsudin, Mad Nasir; Buda, Mark (Faculty of Agriculture, Mulawarman University Samarinda, East Kalimantan, 2023)
Food insecurity occurs whenever the availability and accessibility to obtain adequate and safe food is limited or uncertain. At the national level, Malaysia is considered as food secure, however, at the household level, the food insecurity is still existing especially among the low-income households. Thus, the purpose of this study is to determine the coping strategies used among low-income households in order to cope with food insecurity situation. The study also attempts to determine the factors that can influence the low-income households to used harmful coping strategies in Klang Valley, Malaysia. The data was collected among low-income households in Klang Valley and 449 respondents had completed the survey. Four dimensions namely; dietary change, shortterm measures to increase household food availability, short-term measures to reduce the number of people to feed, and rationing strategies were use to establish the Coping Strategies Index (CSI). The findings of this study suggested that 11.36%, 43.21%, 38.75% and 6.68% of the respondents were using low, mildly, moderately and severely coping strategies, respectively. The results suggested that financial and food assistance is required to help this vulnerable group of households to cope with increase in living cost and consequently will help them for a better livelihood.